124k views
0 votes
Solve the system of equations by substituting

15x+31y=−3
x=−y+3


User Likk
by
4.1k points

2 Answers

7 votes

Answer:


x=6


y=-3

Explanation:

Substitute (-y + 3) for x in the first equation:


15(-y+3)+31y=-3

Expand:


45-15y+31y=-3

Simplify:


45+16y=-3

Subtact 45 from both sides:


16y=-48

Divide both sides by 16:


y=-3

Substitute -3 for y in either equation:


x=-(-3)+3


x=6

User Pixelistik
by
4.6k points
2 votes

Answer:

x=6 y=-3

Explanation:

User Marty Mulligan
by
4.7k points